Teaching fundamentals of robotics to computer scientists - Aliane, Nourdine (Computer applications in engineering education, 2011)
This article presents a methodology to reinforce the teaching of fundamentals of robotics to computer scientists. The pedagogical basis is focused on engaging students in an in‐depth study of the subject using computing in a substantive way. The approach consists in complementing the lectures by programming assignments focused on giving students a deeper understanding of how robotic systems work from the inside. This article presents the author's experience in the use of this approach, as well as a set of proposed assignment projects. © 2009 Wiley Periodicals, Inc. Comput Appl Eng Educ 19: 615–620, 2011